Case Report: Unresectable pulmonary metastases of a giant cell tumor of bone treated with denosumab: a case report and review of literature - Miwa, Shinji; Yamamoto, Norio; Hayashi, Katsuhiro; Takeuchi, Akihiko; Igarashi, Kentaro; Taniguchi, Yuta; Morinaga, Sei; Asano, Yohei; Nojima, Takayuki; Tsuchiya, Hiroyuki (Frontiers in Oncology, 2023)
Giant cell tumors of bone (GCTB) sometimes metastasize to distant organs. In this case report, we present pulmonary metastases of GCTB mimicking malignancies. A 49-year-old man underwent two surgical treatments for a GCTB of the right proximal radius. At the time of the second surgery, no lesions were observed on chest radiography. Three years after surgery, the patient presented with cough and dyspnea, and chest radiography and computed tomography (CT) revealed multiple lung nodules. Positron emission tomography /CT revealed a high accumulation of 18F-fluoro-2-deoxy-Dglucose (18F-FDG) in multiple lesions. Based on the rapid growth and accumulation of 18F-FDG, a metastatic malignant tumor was suspected. CT-guided needle biopsy was performed, and the histology showed proliferation of spindle cells and multinuclear giant cells without malignant changes. Denosumab was administered because multiple lung lesions were unresectable. One month after denosumab treatment, CT showed marked shrinkage of the lesions, and the symptoms significantly improved. Eighteen months after the initial treatment with denosumab, the patient had no symptoms or tumor growth. Although its long-term efficacy and safety remain unclear, denosumab may be a treatment option for patients with unresectable pulmonary GCTB.